Cognitive flexibility and problem-solving in patients with bipolar disorder - Nugroho, Maria Yosepha Safira; Daeng, B. Handoko; Waworuntu, Gladdy L. (Biomolecular and Health Science Journal, 2019)
Introduction: This study focuses on the cognitive impairment in patients with bipolar disorder and also the distribution of cognitive flexibility and problem-solving by degree of education, chronicity, and episode of patient is in at the time of evaluation.Methods: This was a cross sectional descriptive study with purposive sampling method. The population was the Harmony in Diversity Group in Surabaya, Indonesia. Twenty-two patients agreed to be subjects and each of them finished the Wisconsin Card Sorting Test (WCST) to measure cognitive flexibility and the Tower of London (TOL) to measure problem-solving. Results: The WCST score are below normal for 90.9% of the patients. Higher cognitive flexibility is found in patients with bachelor's degree and euthymic patients, while lower cognitive flexibility is found in patients in depression episode, manic episode, and mixed episode. No patients could finish the TOL within the minimum required steps. Better problem-solving is found in patients in manic episode and euthymic patients while lower problem-solving is found in mixed episode and depressive episode.Conclusion: The cognitive flexibility and problem-solving in patients with bipolar disorder are lower than the normal cut off. The type of episode and chronicity are contributing factors. Euthymic patients tend to have better cognitive flexibility and manic patients tend to have better problem-solving ability.